Construct the Validity of STEM and Project-based Critical Thinking Skills Test Instruments Using the Rasch Model - Rina Dwi Setyawati; Binod Prasad; Agnita Siska Pramasdyahsari; Sindi Nur Aini (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Students' critical thinking skills are very important abilities in the 21st century. To measure critical thinking skills, a valid and reliable instrument is needed. This article uses the Rasch model to construct an instrument for critical thinking skills on number pattern material whose learning uses STEM PjBL. The development method uses the analysis, design, development, implementation, and evaluation (ADDIE) stages. Data processing uses the Rasch model assisted by the Winstep program. The instrument was tested on 33 public junior high school students in Semarang. The research results include validity, namely the validity test by experts with an average percentage of 92.4% in the very valid category, the quality of the questions in the instrument reliability aspect is good, and the average critical thinking ability of students who use STEM-based and Project Based instruments Learning was 61.46, higher than other classes at 49.79. The critical thinking test instrument is based on STEM and the project needs to be further developed on other materials.Keywords: Construct Validity, Critical Thinking Skill, Rasch ModelKemampuan berpikir kritis siswa merupakan kemampuan yang sangat penting di abad 21 ini. Untuk mengukur kemampuan berpikir kritis diperlukan instrumen yang valid dan reliabel. Tujuan penelitian ini adalah mengembangkan instrument tes kemampuan berpikir kritis yang berbasis STEM dan proyek. Soal terdiri dari 15 item materi aritmatika sosial yang memuat indikator Focus, Reason, Inferent, Situation, Clarity dan Overview. Metode pengembangan menggunakan tahapan analysis, design, development, implementation, and evaluation(ADDIE).Pengolahan data menggunakan model Raschberbantuan program Winstep. Instrumen diujicobakan pada 33 siswa SMP Negeri diSemarang. Hasil penelitian mencakup valid yaitu pada uji validitas oleh ahli dengan rata-rata persentase sebesar 92,4 % dalam kategori sangat valid, kualitas butir soal pada aspek reliabilitas instrumen baik, dan rata-rata kemampuan berpikir kritis siswa yang menggunakan instrument berbasis STEM danproyeksebesar 61,46 lebih tinggi dari kelas lain sebesar 49,79. Instrument tes berpikir kritis didasarkan pada STEM dan proyek perlu dikembangkan lebih lanjut pada materi-materi lainya.